Challenges and Efforts of School Stakeholders in Enhancing P5 through the Theme “Bangunlah Jiwa Raganya” at SMP Negeri 31 Batam - Sondari, Resti; Rianto, Slamet; Febriani, Trina (Journal of English Language and Education, 2025)
This study is based on the implementation of the Pancasila Student Profile Strengthening Project (P5) as part of Indonesia’s curriculum shift from the 2013 Curriculum to the Merdeka Curriculum. The research aims to identify: (1) the challenges faced by school stakeholders in enhancing P5 through the theme "Bangunlah Jiwa Raganya", and (2) the efforts made to overcome these challenges at SMP Negeri 31 Batam. This is a qualitative study using purposive sampling involving the principal, vice principal, teachers, administrative staff, school committee, and students. Data were collected through observation, interviews, and documentation. The findings reveal key challenges such as lack of facilities, limited collaboration, and insufficient materials. However, the school has responded with several strategies including the use of student smartphones, group-based learning, and peer collaboration to ensure successful P5 implementation. Overall, the project is running smoothly with continuous efforts to improve its delivery.